Tea Consumption, Milk or Sweeteners Addition, Genetic Variation in Caffeine Metabolism, and Incident Venous Thromboembolism - Xiang, Hao; Liu, Mengyi; Zhou, Chun; Huang, Yu; Zhang, Yuanyuan; He, Panpan; Ye, Ziliang; Yang, Sisi; Zhang, Yanjun; Gan, Xiaoqin; Qin, Xianhui (Thrombosis and Haemostasis, 2024)
Objective The association between tea consumption and venous thromboembolism (VTE) remains unknown. We aimed to evaluate the association between tea consumption with different additives (milk and/or sweeteners) and incident VTE, and the modifying effects of genetic variation in caffeine metabolism on the association.Methods A total of 190,189 participants with complete dietary information and free of VTE at baseline in the UK Biobank were included. The primary outcome was incident VTE, including incident deep vein thrombosis and pulmonary embolism.Results During a median follow-up of 12.1 years, 4,485 (2.4%) participants developed incident VTE. Compared with non-tea drinkers, tea drinkers who added neither milk nor sweeteners (hazard ratio [HR]: 0.85; 95% confidence interval [95% CI]: 0.76–0.94), only milk (HR: 0.86; 95% CI: 0.80–0.93), and both milk and sweeteners to their tea (HR: 0.90; 95% CI: 0.81–0.99) had a lower risk of VTE, while those who added only sweeteners to their tea did not (HR: 0.94; 95% CI: 0.75–1.17). Moreover, there was an L-shaped relationship between tea consumption and incident VTE among tea drinkers who added neither milk nor sweeteners, only milk, and both milk and sweeteners to their tea, respectively. However, a nonsignificant association was found among tea drinkers who added only sweeteners to their tea. Genetic variation in caffeine metabolism did not significantly modify the association (p-interaction = 0.659).Conclusion Drinking unsweetened tea, with or without added milk, was associated with a lower risk of VTE. However, there was no significant association between drinking tea with sweeteners and incident VTE.
Keywords: tea consumption; venous thromboembolism; milk; sweeteners; caffeine metabolism